2020
DOI: 10.37520/fi.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

Independent water vole (Mimomys savini, Arvicola: Rodentia, Mammalia) lineages in Italy and Central Europe

Abstract: Water voles are important key fossils of the Quaternary. Given their wide distribution, regional differences were expected to exist in different areas. Early hints on possible independent evolutionary trends of water voles in Italy came from palaeontology and specifically from the comparison of enamel differentiation (SDQ value) of the first lower molars between specimens from Italy and Germany. The data available at that time indicated that in the early Middle Pleistocene there were only minor enamel differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Maul et al (1998) consider it impossible for the populations of peninsular Italy to belong to a "northern" evolutionary lineage and classify the late Pleistocene populations of southern Italy as Arvicola sp. (see also Masini et al, 2003) a position accepted by Piras et al (2012). Recently, Castiglia et al (2016) demonstrated the existence of a divergent mtDNA lineage for the populations of Arvicola amphibius (s.l.)…”
Section: Aves Indetmentioning
confidence: 93%
“…Maul et al (1998) consider it impossible for the populations of peninsular Italy to belong to a "northern" evolutionary lineage and classify the late Pleistocene populations of southern Italy as Arvicola sp. (see also Masini et al, 2003) a position accepted by Piras et al (2012). Recently, Castiglia et al (2016) demonstrated the existence of a divergent mtDNA lineage for the populations of Arvicola amphibius (s.l.)…”
Section: Aves Indetmentioning
confidence: 93%
“…The systematics of the genus Arvicola has also been discussed and reviewed. Maul et al (1998) pointed out that the morphology of the M 1 from the southern Italy Arvicola populations would not belong to the same evolutionary line of the transalpine populations, a thesis reiterated by Masini et al (2003). Molecular studies (Taberlet et al, 1998;Piertney et al, 2005;Kryštufek et al, 2015) revealed that the evolutionary history of the genus Arvicola is more complicated than the previously proposed models (see cladograms in Taberlet et al, 1998and Pirtney et al, 2005, combined in Marcolini et al, 2011and Piras et al, 2012.…”
Section: Arvicola Italicusmentioning
confidence: 98%
“…A general decrease in the value of SDQ index is observed in water vole populations all across Europe during the Middle and Late Pleistocene (Heinrich 1990;van Kolfschoten 1992;Koenigswald von 1994;van Kolfschoten and Turner 1996;Desclaux et al 2000;Maul et al 2000;Paunescu et al 2004;Kalthoff et al 2007;Cuenca-Bescós et al 2010). However, this trend is not perfectly smooth through time or synchronous in all regions (Maul and Markova 2007;Maul et al , 2014Masini et al 2020). Hence, criticisms have been made about the use of the SDQ index as a tool for specific determination and/or stratigraphic correlations (Escudé et al 2008;Martin 2014).…”
Section: Small Mammals: Biochronological Inferencesmentioning
confidence: 99%